Dietary behaviours and the mental well‐being of New Zealand adolescents. (10th April 2017) - Puloka, 'Ilaisaane; Utter, Jennifer; Denny, Simon; Fleming, Terry
Abstract : Aim: To examine the associations between diet and mental health indicators in adolescents. Methods: Data were drawn from the Youth 2012 survey, a national survey of the health and well‐being of adolescents in New Zealand ( n  = 8500). Multiple regression models were used to determine the associations between healthy and unhealthy eating and mental health indicators while adjusting for sex, age, ethnicity, small area deprivation and household poverty as covariates. Results: Approximately 30% of young people in the lowest quartile for healthy eating reported significant depressive symptoms. Greater healthy eating was significantly associated with fewer depressive symptoms, better well‐being and fewer emotional difficulties (all P  < 0.001 after adjusting for covariates). Greater unhealthy eating was significantly associated with greater depressive symptoms, poorer well‐being and greater emotional difficulties (all P  < 0.001 after adjusting for covariates). Conclusions: Findings from this study contribute to a growing body of literature that indicate that eating behaviours are associated with mental health indicators among adolescents. Findings from the current study suggest that efforts to enhance healthy eating may also have a positive impact on mental health.